Precoder design for distributed antenna systems (DAS) with limited channel state information - Hieu Duy Nguyen; Jingon Joung; Sumei Sun (2015 IEEE International Conference on Communications (ICC), 2015)
A distributed antenna system (DAS) consists of multiple baseband units (BBUs) connecting to distributed antennas (DAs) via dedicated access links. In this study, we investigate a DAS with limited channel state information (CSI) and consider an average rate of users as an objective, where the expectation is taken over the channel uncertainty. We propose two distributed precoder designs that are based on a rate lower bound and a rate upper bound, respectively. As a benchmark, coordinated precoder and cooperative dirty paper coding (DPC)-based precoder with full CSI are compared with our proposed algorithms. Numerical results verifies that the rate performance of our upper-bound based scheme with limited CSI approaches tightly the maximum rates of the full CSI schemes, while that of lower-bound based scheme is relatively worse.